Prevalence, methods of rapid weight loss amongst elite Japanese wrestlers: a questionnaire-based study of the 2016 Japanese Wrestling Championship - Nishimaki, Mio; Teo, Cheryl; Nakajima, Kohei; Yamashita, Daichi; Kondo, Emi (Journal of High Performance Sport, 2020)
This study aims to investigate weight loss practices of elite Japanese wrestlers who participated at the 2016 Japanese Wrestling Championship. In this study, we defined rapid weight loss (RWL) as losing 5% or more of their weight relative to their intended weight class, one week before weigh-in. 241 wrestlers completed a questionnaire on their weight loss practices. 109 wrestlers reported RWL and were used for analysis. We found that wrestlers who cut weight over a longer duration utilized a greater variety of weight loss methods than those who cut weight over a shorter duration. Reduced carbohydrate intake was commonly used by wrestlers who cut weight over a longer duration utilized a greater variety of weight loss methods than those who cut weight over a shorter duration. Dehydration was commonly done by all wrestlers. We also identified that the use of low carbohydrate and low salt diets are not optimized for RWL, and suggest for wrestlers to be educated to improve the effectiveness of these methods. Studies to investigate the revision of the weigh-in rules are recommended to better understand the implications of these changes on RWL and recovery practices in wrestlers.